A Module of Systematic Desensitization Guidance and Counseling to Reduce Learning Anxiety of Junior High School Students - Hulukati, Wenny; Hulukati, Evi; Puluhulawa, Meiske (Technium Social Sciences Journal, 2023)
Generated from the problem statement, the present study aimed to produce a module of systematic desensitization guidance and counseling as a medium to reduce the learning anxiety of junior high school students. It relied on a Research and Development method by Sugiyono, limited to seven stages: (1) potential and problem, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trial, (7) product revision. The expert subject consisted of the experts of guidance and counseling media, guidance and counseling, and Indonesian language. Meanwhile, the small-group trial subject involved four teachers of guidance and counseling. The data were primarily collected from a questionnaire and were analyzed qualitatively (content analysis) and quantitatively (t-test). The results of the expert validation and the small-group trial showed that the module of systematic desensitization guidance and counseling was feasible and practical as a medium to reduce the learning anxiety of junior high school students.